Immune cell ratio and coagulation markers in assessing prognosis of asthma: a cross-sectional study from Saudi Arabia - Aldakheel, Fahad M.; Alruwaili, Zamil A.; Alduraywish, Shatha A.; Alshammary, Amal F.; Mateen, Ayesha; Syed, Rabbani; John, James (Frontiers in Immunology, 2023)
Asthma affects a significant number of individuals in Saudi Arabia, with increasing prevalence worldwide, leading to a considerable impact on their quality of life and frequent hospitalizations. In this study, we aimed to explore the relationship between the immune cell ratio and coagulation markers, specifically to identify the occurrence of coagulation abnormalities associated with asthma. To achieve this, we assessed asthma history and severity using a questionnaire while analyzing coagulation biomarkers through venous blood samples. The biomarkers examined included d-dimer, prothrombin time (PT), partial thromboplastin time (PTT), and the international normalized ratio (INR). In addition, we evaluated various hematological parameters such as blood cell counts and hemoglobin (HGB) levels. Our findings revealed compelling evidence, showing significantly elevated levels of d-dimer and the eosinophil-to-neutrophil (ENR) ratio in asthma cases compared to the controls. Moreover, we observed a positive correlation between d-dimer levels and the ENR, with each unit increase in d-dimer associated with a 0.0006 increase in the ENR among asthma cases. These results highlight the potential of assessing ENR and d-dimer levels as predictive indicators for disease prognosis and the development of coagulation abnormalities in individuals with asthma. By shedding light on the relationship between immune cell ratios and coagulation markers in the context of asthma, our study contributes to a better understanding of disease progression and the associated complications. These insights can potentially lead to improved management strategies and better outcomes for asthma patients.